Pre-Analytical Stability of Fasting Blood Glucose: A Comparison Between Immediate Analysis and Two-Hour Room Temperature Storage - Sugito, Sugito; Djohan, Herlinda; Tumpuk, Sri; Sidiq, Alfino Validita; Agum, Dexa (poltekkes kemenkes pontianak, 2025)
The stability of blood samples for glucose testing is a critical preanalytical factor. In vitro glycolysis at room temperature can significantly decrease glucose levels, potentially leading to inaccurate diagnostic results. This study aimed to compare fasting blood glucose levels examined immediately and those stored for 2 h at room temperature. This descriptive, cross-sectional study involved 35 serum samples from participants undergoing fasting blood glucose tests at the Sintang Regional Health Laboratory. Each sample was split into two aliquots: one was analyzed immediately after processing (baseline), and the other was analyzed after being stored for 2 hours at room temperature (25-30°C). Glucose levels were measured using the GOD-PAP method with a Microlab 300 spectrophotometer. Statistical analysis was performed using the Shapiro-Wilk normality test and paired T-test to compare the differences in glucose levels between the two groups. The mean glucose level examined immediately was 90.8 mg/dL (SD=5.098), while the level after the 2-hour delay was 85.8 mg/dL (SD=4.451), showing an average decrease of 5.0 mg/dL. The data were normally distributed (p=0.129), and the paired T-test showed a highly statistically significant difference (p<0.001) between the two examination conditions. Storing serum samples at room temperature for 2 h significantly decreased glucose levels. This finding underscores the importance of immediate sample processing for glucose testing to ensure accurate diagnosis. If a delay is unavoidable, sample refrigeration is highly recommended to inhibit the glycolysis process.